Disseminate of handout based on guided discovery method in terms of student learning motivation - S Nerita; Y S Hartati; A Maizeli; A Afza (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The research team has developed handout based on guided discovery method in process evaluation and learning outcomes of biology subject. Development has resulted handout that valid, practical, effective, and disseminate stage will be carried out. The disseminate stage is done at Program Studi Pendidikan Biologi Sekolah Tinggi Keguruan dan Ilmu Pendidikan Ahlussunnah Bukittinggi, Sumatera Barat. This study aims to determine student learning motivation by using products that have been developed. This is a development research using a 4D model, which is in disseminate stage. The instrument used is student learning motivation questionnare. The questionnare was filled out by students of Program Studi Pendidikan Biologi STKIP Ahlussunnah who have taken the course of process evaluation and learning outcomes of biology subject as many as 20 students, and the data is processed using a percentage formula. The results showed that the average student learning motivation after using the handout was 81,18% (very effective). It can be concluded that at disseminate stage, handout based on guided discovery method in process evaluation and learning outcomes of biology subject have been effectively seen from student learning motivation.